Hip hemiarthroplasty using major lower limb nerve blocks: A preliminary report of a case series - Ahmad Muhammad Taha; Mohammed Abd-Elfttah Ghoneim (Saudi Journal of Anaesthesia, 2014)
Background: Major lower limb nerve blocks are relatively safe techniques. However, their efficacy for hip hemiarthroplasty is unknown. The objective of this study was to determine the effectiveness of combined femoral, sciatic, obturator and lateral femoral cutaneous (LFC) nerve blocks in providing adequate anesthesia for hip hemiarthroplasty. Materials and Methods: A total of 20 patients with fracture neck femur; who underwent hip hemiarthroplasty, participated in this observational study. In the induction room, all patients received ultrasound-guided femoral, proximal obturator, LFC and parasacral sciatic nerve blocks in addition to local infiltration at the proximal site of the skin incision. Anesthesia was considered to be adequate only if the surgery was completed without any requirement for opioid administration. Results: All patients (100% [95% confidence interval, 86-100%]) had adequate anesthesia. Seventeen patients (85% [95% confidence interval, 63-96%] had mild discomfort during the reduction of the prosthetic femur head back into the hip socket; however, no supplementary analgesics were required. Conclusion: The combined femoral, sciatic, obturator and LFC nerve blocks in addition to local infiltration at the proximal site of skin incision could provide adequate anesthesia for hip hemiarthroplasty. Light sedation before reduction of the prosthetic femur head back into the hip socket is advisable.